An Analysis of Pronunciation Speech Error Produced by First Semester Student in Retelling the Contents of Maudy Ayunda’s Youtube Channel - Hilmalia Putri; Dinar Vincy Yunitaka Bahrudin; Linta Wafdan Hidayah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to analyze the pronunciation errors produced by first-semester students in retelling the content of Maudy Ayunda’s YouTube channel. The research focuses on identifying the types of pronunciation errors, determining the dominant errors, and exploring the factors causing these errors. This study employed a qualitative approach with a case study design involving 15 first-semester students of the English Education Study Program. The data were collected through observation, interviews, documentation, and students’ recorded speech, and analyzed using the interactive model of data analysis. The findings reveal that students produce two major types of pronunciation errors, namely segmental and suprasegmental errors. Segmental errors are found to be the most dominant, including substitution, omission, and addition errors in both vowel and consonant sounds. Meanwhile, suprasegmental errors are identified in word stress, intonation, and rhythm, which significantly affect the clarity and naturalness of students’ speech. The study also finds that pronunciation errors are influenced by both linguistic factors, such as first language interference, unfamiliar sounds, and limited vocabulary, and non-linguistic factors, including lack of practice, nervousness, and lack of confidence. In addition, YouTube is found to have a positive role in providing authentic pronunciation input, although its effectiveness depends on active speaking practice. In conclusion, pronunciation errors among first-semester students are complex and influenced by multiple factors. Therefore, an integrated and practice-oriented approach is needed to improve students’ pronunciation accuracy and speaking performance.